1991
DOI: 10.1007/bf01713936
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing transcutaneous oxygen and carbon dioxide measurements in adult intensive care patients

Abstract: Transcutaneous PO2 (PtcO2) is suggested to reflect tissue oxygenation in intensive care patients, whereas transcutaneous PCO2 (PtcCO2) is advocated as a noninvasive method for assessing PaCO2. In 24 critically ill adult patients (mean Apache II score 14.2, SD 4.7) we investigated the impact of variables that are commonly thought to determine PtcO2 and PtcCO2 measurements. A linear correlation was found between PtcO2 and PaO2 (r = 0.6; p less than or equal to 0.0001) and between PtcO2 and mean arterial blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Despite differences in the values of PtcO 2 and PaO 2 , a relationship between these two parameters has been documented (Weaver 2007;Kesten et al 1991). Some authors have shown that the strongest correlation between PtcO 2 and PaO 2 was found for PtcO 2 values measured on the chest (Nishiyama et al 2006;Hasibeder et al 1991). The present results failed to confirm this observation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Despite differences in the values of PtcO 2 and PaO 2 , a relationship between these two parameters has been documented (Weaver 2007;Kesten et al 1991). Some authors have shown that the strongest correlation between PtcO 2 and PaO 2 was found for PtcO 2 values measured on the chest (Nishiyama et al 2006;Hasibeder et al 1991). The present results failed to confirm this observation.…”
Section: Discussionmentioning
confidence: 91%
“…In a report by Weaver (2007) the difference between PtcO 2 and PaO 2 was <10 %, but that study involved healthy subjects in hyperbaric conditions. In reports on transcutaneous gas measurement in severely ill patients, the PtcO 2 /PaO 2 difference was even more pronounced (Hasibeder et al 1991). However, the comparative analysis of results from healthy subjects and patients with various respiratory and circulatory disorders may be misleading and requires caution, as the measurements in the latter can be influenced by hypoperfusion and alterations in tissue metabolism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…attempted the translation of PtcO 2 values to cardiac hemodynamics, when they explored the dependence of PtcO 2 on PaO 2 using a PtcO 2 index (PtcO 2 /PaO 2 ) to assess the severity of low flow shock [6]. A PtcO 2 index below 0.7 has been associated with hemodynamic failure in adult patients [25,26]. The PtcO 2 index has been used to estimate the adequacy of cardiac output and peripheral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Due to pre-existing diseases like diabetic disease, venous or arterial hypertension, pulmonal diseases or different anatomic conditions [23][24][25][26] the mean tissue oxygen tension of each patient differs a lot (e.g. Pat.…”
Section: Discussionmentioning
confidence: 99%